Lutheran Subjectivity and Costly Neighbor Love in Secular Sweden: Confronting the Refugee Crisis through Alethurgy. Issue 3 (4th September 2017) - Thompson, Deanna A.
Abstract: This article offers a constructive Lutheran theology that challenges the hegemony of secular Sweden, particularly in light of challenges posed by the current global refugee crisis. The author uses Guillermo Hanson's creative rethinking of Lutheran subjectivity to highlight a radical embodied vision of neighbor love. Retrieving Luther's claim that Muslims and Christians worship the same God, the article concludes with proposals for alethurgic practices that wed neighbor love to acknowledgement of a common God.